2023
DOI: 10.1177/21582440231159294
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Necessity and Opportunity Motivation Factors in Women Entrepreneurship: A Systematic Literature Review

Abstract: The dichotomy of the Necessity and Opportunity motivation (Push-Pull model) has been frequently used to explain Women Entrepreneurial Motivation (WEM) unvaryingly in most situations. The literature indicates a need for clarity and precision in the context-specific conceptualization of this construct. Understanding the disparities between WEM in developed and developing nations will further clear the ambiguity. The current article addresses this gap in three stages. Systematically analyzing 103 articles publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 131 publications
0
1
0
Order By: Relevance
“…The research results showed that external motivations significantly and positively affect the behaviour of female entrepreneurs in Oman, supporting the first hypothesis. Previous literature emphasized that financial motives often drive individuals to engage in entrepreneurial activities (Lingappa and Rodrigues, 2023). Additionally, factors such as the need for work-life balance, economic necessity due to unemployment or divorce, and familial responsibilities influence women's participation in self-employment (Mitra, 2002;Solesvik et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The research results showed that external motivations significantly and positively affect the behaviour of female entrepreneurs in Oman, supporting the first hypothesis. Previous literature emphasized that financial motives often drive individuals to engage in entrepreneurial activities (Lingappa and Rodrigues, 2023). Additionally, factors such as the need for work-life balance, economic necessity due to unemployment or divorce, and familial responsibilities influence women's participation in self-employment (Mitra, 2002;Solesvik et al, 2019).…”
Section: Discussionmentioning
confidence: 99%